THE PRODUCTION OF THE SPACE, AGRICULTURE AND FOOD: FROM AGRICULTURAL REVOLUTION TO FOOD EMPIRES - Valerio, V. J. O. [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2021)
Since the Neolithic agricultural revolution, the control of food supply has been one of the elements that reference the production of space in the light of human activities, defining, deepening and complexifying structures and society-nature relations. Under the current mechanisms of cooptation and control of food on a global scale, food empires consolidate power structures endowed with the potential to control all activities of production, processing, distribution and consumption of food, which leaves hostages producers and consumers. In this sense, in order to understand the role of food control in the production of geographical space in the past and in the present, I present a brief review of the concepts that structure the analysis, with emphasis on the concepts of space, territory, international dietary regimes and food empires. If historically the emergence of agriculture freed humanity from the arduous task of acquiring the daily food necessary for its sustenance, currently the appropriation of food relations by large international corporations makes food the trump that allows capital to keep captive producers and consumers, which imposes challenges to think of ways to overcome the currently hegemonic food system.
Keywords: Space production; Agriculture; Food; International food regimes; Food empires